2010
DOI: 10.1186/ar3216
|View full text |Cite
|
Sign up to set email alerts
|

Changes in serum and synovial fluid biomarkers after acute injury (NCT00332254)

Abstract: IntroductionAcute trauma involving the anterior cruciate ligament is believed to be a major risk factor for the development of post-traumatic osteoarthritis 10 to 20 years post-injury. In this study, to better understand the early biological changes which occur after acute injury, we investigated synovial fluid and serum biomarkers.MethodsWe collected serum from 11 patients without pre-existing osteoarthritis from a pilot intervention trial (5 placebo and 6 drug treated) using an intra-articular interleukin-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
224
3
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(254 citation statements)
references
References 47 publications
22
224
3
5
Order By: Relevance
“…Finally, we do not have long-term joint aspirations or patient followup to demonstrate if these proteases continue to be present in injured joints and/or lead to posttraumatic OA. .We did not compare our aspiration results with serum results, which has been done in other studies because these studies failed to show good correlations between serum and synovial fluid concentrations [7,14,16]. Also it is possible that our dilution methodology, especially when aspirating joint fluid from a normal joint, could have altered the true levels of degradative products and enzymes in our study.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Finally, we do not have long-term joint aspirations or patient followup to demonstrate if these proteases continue to be present in injured joints and/or lead to posttraumatic OA. .We did not compare our aspiration results with serum results, which has been done in other studies because these studies failed to show good correlations between serum and synovial fluid concentrations [7,14,16]. Also it is possible that our dilution methodology, especially when aspirating joint fluid from a normal joint, could have altered the true levels of degradative products and enzymes in our study.…”
Section: Discussionmentioning
confidence: 89%
“…In an effort to look specifically at the presence of proteolytic enzymes after traumatic injury, several authors have shown elevated MMPs and aggrecan degradation after ACL tear. However, the time from ACL injury to joint aspiration had considerable variability in these studies [5,7,26,30]. There are currently no human studies of which we are aware that quantify the concentrations of MMPs and/or aggrecan degradation acutely after articular fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Parvizi et al [26] reported a high correlation coefficient (r 2 = 0.72) between these two CRP assays in the setting of total joint arthroplasty while Catterall et al [6] reported a positive correlation in patients with acute knee trauma. Catterall et al [6] postulated that diffusion of serum CRP into the joint could be responsible for an elevated synovial fluid CRP when elevated systemically.…”
Section: Discussionmentioning
confidence: 99%
“…Parvizi et al [26] reported a high correlation coefficient (r 2 = 0.72) between these two CRP assays in the setting of total joint arthroplasty while Catterall et al [6] reported a positive correlation in patients with acute knee trauma. Catterall et al [6] postulated that diffusion of serum CRP into the joint could be responsible for an elevated synovial fluid CRP when elevated systemically. Parvizi et al [26] applied this to PJI and theorized that synovial permeability caused by local inflammation may allow for high levels of serum CRP to diffuse into the joint, thus increasing synovial CRP.…”
Section: Discussionmentioning
confidence: 99%
“…Kulmala et al (2012) (GRAUW et al, 2009;CONNOLLY et al, 2012;CATTERALL et al, 2010 Em estudos com artrite reumatoide em humanos, foram encontradas citocinas com poder anti-inflamatório na articulação, são elas interleucina 10 (IL-10), interleucina 4 (IL-4) e interleucina 13 (IL-13). Acredita-se que a IL-10 iniba a liberação dos fatores pró-inflamatórios comentados acima.…”
Section: Fisiologia Do Ambiente Articularunclassified